Bowling action technique differences between elite & sub-elite cricket fast bowlers using 3d biomechanical analysis - Raman, S. A.; Nimishaanth, S. S.; Arun, C.; Thiagarajan, K. A.; Arumugam, S. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Cricket fast bowlers utilise various techniques to help propel the ball faster, including some techniques which carry injury risk. Biomechanical studies have demonstrated technique related factors which can influence performance and injury risk. This study aims to evaluate technique differences between elite and sub elite fast bowlers, to understand the factors contributing to performance and injury risk. METHODS: 15 male Indian elite and 15 sub elite fast bowlers underwent 3D biomechanical analysis of their bowling action in an indoor biomechanics lab. Front foot Peak Vertical Ground Reaction Force (pVGRF), Lateral Trunk Flexion (LTF), Knee Flexion at Front Foot Contact (KF at FFC), Maximum Knee Flexion (MKF) during front foot contact phase, Stride Length (SL), Ball Release Height (BRH) and ball speed were calculated. After tests for normality, the t-test (parametric method for normally distributed variables) & Mann Whitney U test (non-parametric method for variables not following normal distribution) were used to study differences among the groups. RESULTS: Elite bowlers when compared to sub elite bowlers, had significantly higher mean pVGRF (p=0.03), SL (p<0.001), MKF (p=0.02), LTF (p=0.008), BRH (p=0.02) and ball speed (p=0.019). Mean KF at FFC showed no difference between the two groups (p=0.85). CONCLUSION: Elite bowlers bowled with longer stride length and higher ball release height which could contribute to the greater bowling speeds. Elite bowlers demonstrated higher lateral trunk flexion and higher ground reaction forces which carries higher risk of lumbar spine injury. However, elite bowlers also had higher knee flexion during front foot contact phase, which could mitigate injury risk to some extent. These findings are important for injury prevention, however need to be considered along with other factors such as bowling workload, strength & conditioning status and spinal maturity.